GROWTH OF Vernonia ferruginea SEEDLINGS SUBMITTED TO THERMAL STRESS - Amaral, C. L. [UNESP]; Santos, J. [UNESP]; Portugal, C. R. S.; Braga, A. F. [UNESP]; Alves, P. L. C. A. [UNESP] (Univ Federal Vicosa, 2020)
Stress caused by extreme temperatures is one of the main elements that limit the geographical distribution and the seasonal growth of several plants, causing a severe delay in their development, reducing the photosynthetic rate and signaling the synthesis of defense compounds. Considering the current environmental changes and the damages that these changes can cause in plant physiology and growth, the objective of this work was to understand the interactions between temperature, physiology and growth, and to characterize the impact of temperature changes on the initial development of Vernonia ferruginea Less. Seedlings of this species were conditioned in germination chambers at previously adjusted constant temperatures (10, 20, 25, 30, and 35 degrees C) for sixty days, in order to evaluate physiological and growth parameters. The optimum temperature range for the initial growth of V ferruginea is between 25 and 30 degrees C. The stress caused by suboptimal and over-optimal temperatures affected cell homeostasis and caused a delay in the growth and development of seedlings. In stressful situations, growth inhibition and the activation of response mechanisms were observed for the adaptation and maintenance of cellular homeostasis through the accumulation of the proline osmoprotcctant and soluble carbohydrates. Additionally, plants presented a normal development within a wide temperature range, despite the development delay, the change in gas exchanges and the synthesis of substances related to the defense system.
Keywords: biomass allocation; leaf area; gas exchanges